Moderating Effect of Organizational Culture on the Relationship between Absorptive Capacity and Innovation - Chua, Beng Hui (2007)
Organizational absorptive capacity is part of the learning capabilities of organization. To manage the three components of absorptive capacity: knowledge acquisition, knowledge dissemination and knowledge utilization effectively can sustain firm’s innovation. The purpose of this study is to present the concept of the firm’s absorptive capacity as a multidimensional, dynamic construct to test the relationship with innovative capabilities in the context of growth-oriented MSC companies. In addition, this study attempts to determine the moderating effect of organizational culture on the relationships between absorptive capacity and innovative capabilities. The study draws on empirical results from 215 MSC companies using stratified sampling procedure. The hypotheses were tested using Pearson Correlation and Hierarchical Regression analysis to examine the relationship between the three dimensions of absorptive capacity with innovation as well as the existence of moderating effect of organizational culture. Using three instruments adopted from Darroch (2005), Denison & Mishra (1995) and Wang & Ahmed (2004) to measure independent variable: absorptive capacity, moderator: organizational culture and dependent variables: innovative capabilities. The results of the empirical tests give some support to the view that the flow of knowledge is crucial for sustaining innovative capabilities. The regression estimation shows that knowledge dissemination and knowledge utilization were significantly reflected in the firm’s innovative capabilities. In addition, the effects of absorptive capacity on innovative capabilities were found to be moderated by organizational culture. The finding of this study shed some light on the importance of the firm’s ability to acquire, disseminate and utilize knowledge effectively. In order to channel the knowledge acquired externally to innovation, firms need to adopt supportive organizational culture. The manifestation of a positive effect of absorptive capacity on innovation suggest that decision makers should place greater emphasis on the role of knowledge acquisition, knowledge dissemination and knowledge utilization if they want to better account for the innovation in MSC companies.